Learning with Online Teaching Video Cases: Investigating Pre-Service Preschool Teachers’ Perceived Usefulness and Needs - Rongrong Xu; Alfredo Bautista; Weipeng Yang (Education Sciences, 2024)
Extensive empirical research has emphasized the benefits of integrating Online Teaching Video Cases (OTVCs) into pre-service preschool teacher education. However, there is a research gap concerning the perceptions and needs of pre-service preschool teachers regarding OTVCs. This cross-sectional study, therefore, investigated pre-service preschool teachers’ perceptions of usefulness and need pertaining to OTVCs and examined potential differences across course year levels. A self-designed questionnaire survey was completed by 744 participants from the Shandong Province (China), with a focus on five domains: actors showcased in the OTVCs, OTVC-mediated activities, learning facilitators, situations requiring OTVCs, and areas for improvement. The results revealed that the participants identified expert teacher demonstrations and collaborative learning experiences with peers and instructors as the most useful types of OTVCs. They expressed the need for OTVCs to assist them with job preparation and a desire to learn content knowledge and engage with larger communities of preschool practitioners. Interestingly, the findings revealed significant differences among participants of different year levels, with Year 3 participants finding OTVCs more useful and necessary in most domains. These findings will help preschool teacher educators improve the responsiveness of OTVC-based instruction, thereby providing online video resources tailored to the preferences and needs of pre-service preschool teachers.